Discrete element method in polymer processing – Method for development of material models - Landgräber, Jan; Brüning, Florian (Advanced Powder Technology)

Den Schein werfen/wahren. Transdiziplinaritäten und Popkulturforschungen. Ein Übersetzungsraum als Partitur - Flath, Beate; Jacke, Christoph; Schroeter-Wittke, Harald (Transdisziplinäre Räume in den Kulturwissenschaften)

Visualizing Privacy-Relevant Data Flows in Android Applications - Khedkar, Mugdha; Schlichtig, Michael; Mohan, Santhosh; Bodden, Eric (arXiv:2503.16640)
Android applications collecting data from users must protect it according to the current legal frameworks. Such data protection has become even more important since in 2018 the European Union rolled out the General Data Protection Regulation (GDPR). Since app developers are not legal experts, they find it difficult to integrate privacy-aware practices into source code development. Despite these legal obligations, developers have limited tool support to reason about data protection throughout their app development process. This paper explores the use of static program slicing and software visualization to analyze privacy-relevant data flows in Android apps. We introduce SliceViz, a web tool that analyzes an Android app by slicing all privacy-relevant data sources detected in the source code on the back-end. It then helps developers by visualizing these privacy-relevant program slices. We conducted a user study with 12 participants demonstrating that SliceViz effectively aids developers in identifying privacy-relevant properties in Android apps. Our findings indicate that program slicing can be employed to identify and reason about privacy-relevant data flows in Android applications. With further usability improvements, developers can be better equipped to handle privacy-sensitive information.

Pop-Ikonen. Kulturwissenschaftliche Zugänge. - Jacke, Christoph; Schroeter-Wittke, Harald (Popmix, POPkultur und Religion: The Next Generation)

Die drei Rollen der Star-Figur. Sarah Connors Abrechnung. - Jacke, Christoph (POP. Kultur & Kritik)
Keywords: Stars; Sarah Connor; Rollen; Qualitätsjournalismus; Boulevard; Fans

Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology)
Support is a vital resource at every stage of development throughout the lifespan. In the mother-child relationship, the exchange of support is subject to change in relation to the tasks and framework conditions of the current phase of life. While values and norms typically include social expectations, attitudes summarize individual thoughts or feelings. During young adulthood and midlife, attitudes are particularly important for the mutual support between mothers and their adult children when there are no practical framework conditions, such as care needs, that necessitate support. This study uses social exchange theory to examine the mediating role of felt obligation and perceived mutual reciprocity as important attitudes in the well-known relation between mothers and their adult children receiving and giving support. The sample consisted of 598 German adults (aged 20–49, 55.2% female) and 577 mothers (aged 40–87) of these adults; both perspectives were taken into account. The results from the parallel mediation analyses, in which instrumental and emotional support were considered separately, showed a mediating effect of felt obligation on the instrumental support of adult children for their mothers. The emotional support received and given by the adults to their mothers was mediated by felt obligation and perceived mutual reciprocity. The received and given instrumental and emotional support of the mothers to their adult children was mediated by perceived mutual reciprocity. The relevance of the adults' and mothers' different attitudes regarding support later in life is discussed.

The Influence of an Immersive-Collaborative Learning Unit on the Technology Acceptance of 5G and AR of Industrial Mechanic Students - Schäfers, Johannes; Temmen, Katrin (Proceedings of the 27th International Conference on Interactive Collaborative Learning (ICL2024), Volume 4)
Despite its status as a key enabling technology, the adoption of 5G in industry remains limited, mainly due to a lack of expertise, which can be addressed by incorporating 5G training into vocational schools. Since Augmented Reality (AR) faces similar challenges, it is used as the 5G application. This research aims to determine the extent to which a learning unit using 5G and AR for collaborative work can increase the intention to use these technologies in the vocational setting and gathers the factors that make up 5G acceptance. It is based on the Technology Acceptance Model 2 (TAM2). The sample includes 23 industrial mechanics students who participated in the developed learning unit. All items are scored on seven-tiered Likert scales (0 “totally disagree”; 6 “totally agree”). The results showed a non-significant change in behavioural intention to use 5G, with a mean of 4.95 (SD: 1.18) for the pre-test and 4.43 (SD: 1.68) for the posttest. The change in intention to use AR did not change significantly either, from 3.12 (SD: 1.38) at pre-test to 3.37 (SD: 1.16) at post-test. The factors Perceived Usefulness, Image, and Relevance had the lowest mean scores, indicating areas for targeted improvement. The significant change in Output Quality ratings is likely to reflect initial overestimation by students. The difference in Behavioural Intentions between 5G and AR suggests that AR may not be an effective technology for increasing 5G adoption in educational contexts. One recommendation is to address 5G in the learning unit not only indirectly.
Keywords: 5G; Key Technology; TAM · Augmented Reality; VET

Mg dopants in lithium niobate: Defect models and impact on domain inversion - Bocchini, Adriana; Rüsing, Michael; Bollmers, Laura; Lengeling, Sebastian; Mues, Philipp; Padberg, Laura; Gerstmann, Uwe; Silberhorn, Christine; Eigner, Christof; Schmidt, Wolf Gero (Physical Review Materials)

Inconsistency Handling in DatalogMTL - Bienvenu, Meghyn; Bourgaux, Camille; Khodadaditaghanaki, Atefe (Proceedings of the Thirty-Fourth International Joint Conference on Artificial Intelligence, IJCAI-25)

Vom Prompt zur Praxis – Kooperatives Seminarkonzept zur KI-gestützten Unterrichtsentwicklung in der gewerblich-technischen Lehramtsausbildung - Schäfers, Johannes; Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin

Guidance on Dataspaces: Development of a Learning Environment for Industrial SMEs - Lick, Jonas; Lamarz, Jessica; Dohmann, Friederike; Kulkarni, Pranav Jayant; Zerbin, Julian; Koldewey, Christian (2024 6th International Conference on Control and Robotics (ICCR))
The rapid advancements in digital transformation have led to the emergence of dataspaces as a pivotal element for industry-wide and cross-industry data integration and interoperability across various businesses. Despite their potential, the adoption and effective utilization of dataspaces by business stakeholders remain challenging. This paper aims to address this gap by developing a comprehensive learning environment tailored for business stakeholders. Through an interview study and an analysis of the current state of research, we identify problem fields and derive key requirements for the development of the learning environment. The proposed environment includes a demonstrator and a training concept designed to enhance stakeholders' understanding and capabilities in managing and leveraging dataspaces. Our findings contribute to the body of knowledge by providing practical guidance through learning environments for the deployment of dataspaces in business contexts and highlighting areas for future research.

Untersuchung von Kombinationen aus Duroplasten und Elastomeren für den einstufigen 2K-Spritzgießprozess - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (Technomer 2025 - 29. Fachtagung über Verarbeitung und Anwendung von Polymeren)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

Direkthaftung statt Klebstoff –Verbund von Duroplasten und Kautschuk im 2K-Spritzgießprozess - Löhr, Florian (AZuR-Kolloquium 2025)

Thermoset–Rubber 2K Composite Systems: Material Combinations and Interfacial Reactions in a One-Step Injection Molding Process - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

Improvement of a numerical two-phase simulation model for single-screw plasticizing extruders based on experimental investigations - Knaup, Felix; Schöppner, Volker (International Polymer Processing)
Keywords: CFD simulation; melting modeling; melting process; polymer extrusion; single-screw extruder

Improving an Analytical Model of Melting in Single Screw Extruders considering the Delay Zone Length - Knaup, Felix; Brüning, Florian; Schöppner, Volker (Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2025))
Keywords: Aufschmelzen; Aufschmelzmodellierung; delay zone; extrusion; melting modeling

Bestimmung der Feststoffbettfestigkeit zur Vorhersage von Feststoffbettbrüchen im Einschneckenextruder - Knaup, Felix; Brüning, Florian; Schöppner, Volker (Technomer 2025 29. Fachtagung)
Keywords: Aufschmelzen; Aufschmelzmodellierung; Feststoffbett; melting modeling

Characterization of the wall slip behavior of filled rubber compounds considering the critical wall shear stress - Kleinschmidt, Dennis; Schöppner, Volker (RubberCon 2025)
Keywords: Kautschuk; Rheologie; Wandgleiten

Findings on pinless screw design for rubber extrusion - Schmidt, Leon; Schöppner, Volker; Brüning, Florian (RubberCon 2025)
Keywords: extrusion; Kautschuk; Simulation

Investigation of alternative pinless screw concepts for rubber extrusion - Schmidt, Leon; Brüning, Florian (KGK - Kautschuk Gummi Kunststoffe)
Keywords: extrusion; Kautschuk